A novel pathogenic DICER1 gene variant is associated with hereditary multinodular goiter in an Argentine family as evidenced by clinical, biochemical and molecular genetic analysis - Targovnik, Héctor M.; Barh, Debmalya; Papendieck, Patricia; Adrover, Ezequiela; Gallo, Ariel M.; Chiesa, Ana; Marques Da Silva, Wanderson; Azevedo, Vasco; Rivolta, Carina M. (Springer, 2025)
DICER1 syndrome is an autosomal-dominant disorder that results in malignant or benign tumors. A number of distinct pathogenic germline and somatic variants have been identified as causing multinodular goiter (MNG). The purpose of the present study was to identify and characterize the genetic cause underlying the familial form of MNG through a whole-exome sequencing (WES) analysis in an Argentine family with three affected siblings. Clinical, biochemical and molecular genetics as well as bioinformatics analysis were performed. A novel heterozygous variant in the DICER1 gene was identified in the proband patient by WES. The variant was a single guanine deletion at nucleotide position 2,042 (NM_177438.3:c.2042del) resulting in a frameshift at amino acid 681 with a putative premature stop codon [NP_803187.1:p.Gly681ValfsTer4]. Family segregation analysis showed that his affected sister and his affected brother also were heterozygous for same variant, whereas the father was a healthy heterozygous carrier of the variant and the healthy mother harbor only wild-type alleles in the DICER1 gene. We have also observed that the frameshift variant does not interfere with the pre-mRNA splicing of the exon 13. In addition, two clinically relevant heterozygous variants, not associated with thyroid disease, were also identified in index sibling using the Franklin platform, a frameshift [NP_000234.1:p.Thr55AsnfsTer49] in the MEFV gene (familial mediterranean fever) and a missense [NP_004530.1:p.Ala422Thr] in the NARS1 gene (neurodevelopmental delay and ataxia). In conclusion, in the present study we have identified a novel frameshift variant corresponding to NP_803187.1:p.Gly681ValfsTer4 in the DUF 283 domain of DICER1. The results were in accordance with previous observations confirming the genetic heterogeneity of DICER1 syndrome. Moreover, the identification of this variant in the unaffected father substantiates the hypothesis of incomplete/reduced penetrance.